LA SICUREZZA ALIMENTARE NEL CODICE PENALE TRA TUTELA DELLA SALUTE E TUTELA DEL COMMERCIO (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
In 2002 a new path and evolution about the European Food Legislation started. As a matter of fact, the European Regulation n.178/2002/CE establishes rules, procedures and a pioneering approach regarding food safety. That is automatically introduced and applied in each EU State. Anyway, the European Legislation must 'cross' with national provisions, contained in Penal Code, concerning the protection of human health and of trade. In this paper the Authors outline the "food rules" contained in the Italian Penal Code and analyze the 'parallel convergences' with the EU Rules subjected to direct application, such as the EU Regulations.